Intimate Partner Violence Victimization: Assessing the Applicability of Social Interactionist Theory - Zavala, Egbert (Crime & delinquency, 2025)
A growing body of research has applied Felson’s social interactionist theory to understand violent victimization. The theory claims that individuals experiencing stressful life events or negative affective states behave in an aversive demeanor and this behavior motivates others to attack them. Since its inception, however, this framework has not been applied extensively to intimate partner violence (IPV) victimization. Using data collected from the International Dating Violence Study, the present study tested Felson’s social interactionist theory by examining the direct and indirect effects of stressful conditions, negative affective states, and aversive demeanor on IPV victimization. Results revealed that social interactionist theory of victimization modestly explained the relationship between stressful conditions and IPV victimization. Implications for theory, research, and policy are discussed.